2000
DOI: 10.1111/j.1572-0241.2000.03190.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Morphology, Function, and Quality of Life After Extracorporeal Shockwave Lithotripsy and Endoscopic Treatment of Chronic Calcific Pancreatitis

Abstract: Besides pain relief, ESWL in combination with interventional endoscopy resulted in pancreatic ductal decompression, weight gain, and improvement in quality of life in a considerable number of patients with advanced CCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(77 citation statements)
references
References 30 publications
3
72
2
Order By: Relevance
“…In our study involving Italian patients with chronic pancreatitis [20], neither the type of pancreatic surgery nor endoscopic therapy were able to substantially modify the various physical and mental domains investigated by the SF-36 and this is in contrast to previous studies regarding the various surgical and endoscopic options [4,16,[22][23][24][25][26][27][28][29]; the difference may be due to the fact that these latter studies [4,16,[22][23][24][25][26][27][28][29] enrolled a highly selected group of patients with a short time interval between the intervention and the assessment of the health-related quality of life or that the data were not adjusted for sex and age.…”
Section: Chronic Pancreatitiscontrasting
confidence: 99%
“…In our study involving Italian patients with chronic pancreatitis [20], neither the type of pancreatic surgery nor endoscopic therapy were able to substantially modify the various physical and mental domains investigated by the SF-36 and this is in contrast to previous studies regarding the various surgical and endoscopic options [4,16,[22][23][24][25][26][27][28][29]; the difference may be due to the fact that these latter studies [4,16,[22][23][24][25][26][27][28][29] enrolled a highly selected group of patients with a short time interval between the intervention and the assessment of the health-related quality of life or that the data were not adjusted for sex and age.…”
Section: Chronic Pancreatitiscontrasting
confidence: 99%
“…According to some studies [36,65,67], endoscopic therapy was not able to modify the various physical and mental domains evaluated by both the SF-36 [36,65] and SF-12 [67] questionnaire, whereas endoscopic therapy combined with ESWL was able to significantly improve some QoL scores (pain, weight loss, fever and jaundice) and the global QoL in about 70% of patients during a short time interval (median 7 mo, range: 5−9). Endoscopic therapy can affect the long-term clinical outcome by decreasing both the hospitalization rate for pain and the intake of analgesics [172,173]. Because of the frequent coexistence of different ductal lesions in the same patient, the effectiveness of endoscopic therapy is usually the result of combined procedures, such as sphincterotomy, stricture(s) dilation, stone(s) extraction, stent(s) placement.…”
Section: E2mentioning
confidence: 99%
“…ESWL overcomes the problem of the stone size by fragmenting the stones, thus facilitating endoscopic clearance of the duct. ESWL is required in 36−68% of patients and successful rates of stone clearance of the main pancreatic duct ranged from 37% to 100% [115,120,173,[179][180][181][182][183][184][185][186][187]. Use of ultrasound instead of x-rays to locate pancreatic stones is associated with a lower fragmentation rate [188,189].…”
Section: E3: Is Endoscopic Therapy Indicated In Chronic Pancreatitismentioning
confidence: 99%
“…In Europe, ESWL is employed either primarily or secondarily after failure of endoscopic pancreatolithotripsy. 17,18 Recently, Delhaye 19 reported that ESWL can be used as a first-line treatment when obstructive ductal stones cause Chronic pancreatitis: new developments dilation of the main pancreatic duct (MPD) upstream. In Japan, ESWL is predominant with endoscopic treatment used adjunctively; 12,13,20,21 fragments of pancreatic stones pulverized by ESWL are collected using basket catheters.…”
Section: Treatment Of Chronic Pancreatitismentioning
confidence: 99%